1982
DOI: 10.1093/ajcn/36.1.178
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity indices in children

Abstract: On the basis of a longitudinal study of growth in French children, we attempted to find a valid index for estimating adiposity, and to specify the optimal conditions for its use. The Quetelet index was found suitable for application to children, but as with all methods, a certain lack of precision proved unavoidable because of the different stages of growth observed at a given age. For use by clinicians, we provide charts, based on the Quetelet index and on age, permitting estimation of adiposity in any child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
233
0
19

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 492 publications
(264 citation statements)
references
References 9 publications
12
233
0
19
Order By: Relevance
“…As it is highly correlated with weight and body fat, and weakly related to stature, the weight/(height) 2 , Quételet or body mass index (BMI) has been selected to predict adiposity in children. 6 In the early 1980s, the first BMI distribution reference charts, 6 revised 10 years later, 7 were constructed for all ages throughout childhood ( Figure 1) and adulthood. 7 This method is now used worldwide.…”
Section: Assessment Of the Age At Adiposity Reboundmentioning
confidence: 99%
See 2 more Smart Citations
“…As it is highly correlated with weight and body fat, and weakly related to stature, the weight/(height) 2 , Quételet or body mass index (BMI) has been selected to predict adiposity in children. 6 In the early 1980s, the first BMI distribution reference charts, 6 revised 10 years later, 7 were constructed for all ages throughout childhood ( Figure 1) and adulthood. 7 This method is now used worldwide.…”
Section: Assessment Of the Age At Adiposity Reboundmentioning
confidence: 99%
“…[11][12][13][14][16][17][18] Using the French sample 6,19 of the International Growth Study, 20 we established that age at AR was significantly associated with BMI level at later ages: 4 the earlier the AR, the higher the BMI or the subscapular skin fold at age 21 years. 8 Regression analysis performed on this sample indicated that each year decrease in age at AR was associated with a 0.84 kg/m 2 (0.82 in boys and 0.85 in girls) increase in the predicted BMI level at age 21 years (Po0.001) (unpublished data).…”
Section: Assessment Of the Age At Adiposity Reboundmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect measures of adiposity, such as skinfold thickness and weight for height indices, are often used as proxy measures of adiposity or as criteria for defining obesity. One such indicator, Quetelet's Index (Wt/ Ht 2 ) (Quetelet, 1871), also known as Body Mass Index (BMI), has been shown to be more valid than Wt/Ht or Wt/ Ht 3 in children (Rolland-Cachera et al, 1982), and has been adopted in adults (Garrow and Webster, 1985). Obesity is defined as an excess of fat, and the obese child runs an increase risk of becoming an obese adult (Dietz, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The age-and sex-specific 50th percentile of BMI is derived from nomograms. 31 By this method, the BMI can be expressed independently from age and sex and, therefore, physiological developmental stage. The average RBMI was 165.6±24.7% before treatment.…”
Section: Study Groupmentioning
confidence: 99%